2017
DOI: 10.1039/c7cp04999d
|View full text |Cite
|
Sign up to set email alerts
|

The structure of coronene cluster ions inferred from H2 uptake in the gas phase

Abstract: Mass spectra of helium nanodroplets doped with H and coronene feature anomalies in the ion abundance that reveal anomalies in the energetics of adsorption sites. The coronene monomer ion strongly adsorbs up to n = 38 H molecules indicating a commensurate solvation shell that preserves the D symmetry of the substrate. No such feature is seen in the abundance of the coronene dimer through tetramer complexed with H; this observation rules out a vertical columnar structure. Instead we see evidence for a columnar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 63 publications
5
11
0
Order By: Relevance
“…Using the energetic definition, the results obtained for the single stack motifs over assemblies containing between one and four coronene molecules show approximately linear variations that are consistent with those reported experimentally by Goulart and coworkers, 31 providing further support for the stacking between successive molecules with an incremental shift. The magnitude of this shift inferred by these authors, which is of the order of the aromatic cycle, remains lower than the value in our model of coronene assembly by about 1 Å.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Using the energetic definition, the results obtained for the single stack motifs over assemblies containing between one and four coronene molecules show approximately linear variations that are consistent with those reported experimentally by Goulart and coworkers, 31 providing further support for the stacking between successive molecules with an incremental shift. The magnitude of this shift inferred by these authors, which is of the order of the aromatic cycle, remains lower than the value in our model of coronene assembly by about 1 Å.…”
Section: Discussionsupporting
confidence: 85%
“…The approximate linear slopes that can be extracted in both cases are 11.3 and 10.0 per coronene molecule, respectively. In their mass spectrometry study, Goulart and coworkers 31 reported a slightly higher slope of 11.4 per coronene, which remains in reasonable agreement with our own data for the parallel displaced motif while being at variance with the slope obtained for the rotated stack motif along a common axis.…”
Section: Relation To Stacking Shiftsupporting
confidence: 90%
See 2 more Smart Citations
“…They often correlate with closure of solvation shells, subshells, or second or even third solvation shells [ 43 45 ]. An interesting situation arises if M ± is a planar ion, e.g., coronene; the approximate structure of coronene cluster ions has been inferred from magic numbers in the abundance distributions of He m M 2 + , He m M 3 + , and He m M 4 + [ 46 ].…”
Section: Resultsmentioning
confidence: 99%